Contribution to the design of hydraulic lime-based grouts for masonry consolidation - Baltazar, Luis G.; Henriques, Fernando M. A.; Cidade, Maria Teresa (Journal of Civil Engineering and Management, 2015)
Grout is a concentrated suspension that can be employed for the homogenisation and consolidation of systems presenting pores, voids and cracks, such as inner core of old stone masonries. A grout should be well conceived, taking into account the optimisation of its performance; this means that simple binder and water formulations prove to be inadequate. Hence, the effect of different admixtures and pozzolans, which are traditionally used in concrete, on the fresh and hardened properties of hydraulic lime grouts, were investigated. Hydraulic lime binder plays a role of great importance in the rehabilitation of historic structures, due to its compatibility with pre-existing materials, like mortars. However, hardly any information is presently known regarding the effect of these materials on the behaviour of hydraulic lime grouts. The improvement of their properties through the use of these products is still an open field. Hence, and as a first step, the prediction of grout properties in a laboratory setting were made. The results summarised in this paper are part of a large research project and precede the fine tuning of grout composition according to the characteristics of the masonry to which such a grout is to be injected.